Türkiye’de kooperatifçiliğin tarihi gelişimi ve cumhuriyet dönemi kooperatifçiliği - Özcan, Orhan (My University, 2007)
TÜRKİYE’DE KOOPERATİFÇİLİGİN TARİHİ GELİŞİMİ VE CUMHURİYET DÖNEMİ KOOPERATİFÇİLİĞİ Son yıllarda Türkiye’de ki ve diger ülkelerde ki kooperatif sirketler faaliyet gösterdikleri ülkelerin ekonomilerini yönlendiren önemli aktörlerden birisini haline gelmeye baslamıslardır. Ülkemizde ki kooperatifçilik faaliyetleri önemli gelismeler göstermis olmasına ragmen, günümüzde istenilen seviyede degildir. Bu çalısma ile Türkiye’de Kooperatifçiligin Cumhuriyet Dönemi tarihsel gelisimi anlatılmaya çalısılmıstır. Cumhuriyet Döneminde kooperatifçilik, Atatürk zamanında önemli atılımlar yapmıstır. Ayrıca, 1961 Anayasasıyla, kooperatiflerin gelistirilmesinin devletin sorumluluguna girmesinden sonra kooperatifçilikle ilgili maddeler, Hükümet Programlarında ve Bes Yıllık Kalkınma Planlarında yer almaya baslamıstır. Günümüzde 26 farklı alanda 89.964 kooperatif faaliyet göstermektedir. Bu kooperatiflerin üye sayısı ise 8.709.756 dır. Cumhuriyet Dönemi boyunca kooperatiflerin temel sorunları arasında kooperatif egitiminin çok yetersiz olusu ve maddi kaynak yetersizlikleri göze çarpmaktadır.

THE DEVELOPMENT OF THE COOPERATIVE SYSTEM IN TURKEY AND COOPERATIVES DURING PERIOD OF REPUBLIC During last few years, the cooperative companies both in Turkey and abroad have became one of the leading economic factors in their countries. Although the cooperative activities had a great succes, they are not at the estimated level. With the ease of this work it has been tried to be explained that the historical improvements of the cooperative system during Period of Republic. During Period of Republic, cooperative activities had a considerable progress. Besides, with the Law Constitution of 1961, after improving the cooperatives have become the state’s responsibility, the sections which are related to cooperatives have began taking part in Government Programs and Five Years’ Development Plan. In our time, in 26 different field, 89.964 cooperatives are active. The number of the membership of these cooperatives are 8.709.756. During the Period of Republic, among the basic problems of cooperatives the inadequecy of cooperative education and lack of economical sources can be observed.
Keywords: Kooperatifçilik_Tarih; Türkiye_Kooperatifçilik_Tarih